Accessory pollen adhesive from glandular trichomes on the anthers of Leonurus sibiricus L. (Lamiaceae) - Moyano, Fernando (2003)
We studied six populations of the hummingbird-pollinated Nicotiana glaucato determine if the marked differences in the degree of floral-pollinator mismatch between populations promote divergences in the pattern of pollinator-mediated phenotypic selection on single traits and on the evolution of complexes of many interacting floral traits. We found evidence that flower phenotype is being shaped by pollinator-mediated phenotypic selection, since corolla length was consistently under contemporary directional or stabilizing selection. Weak directional selection for longer corollas was found in two populations with low fl ower?pollinator mismatch; much stronger directional selection was detected for shorter corollas in two populations with high flower?pollinator mismatch; finally, the remaining two populations with intermediate fl ower?pollinator mismatch showed stabilizing selection for corolla length. N. glaucapopulations differed in every flower character measured but variations in pollinator-mediated selection among populations were only observed for corolla length. Multiple covariation among traits was favoured, as suggested by the predominately functional patterns of integration and selection of complexes of many interacting fl oral traits. Th is was consistent with the patterns of correlational selection exhibited by four of the six populations, where corolla length was under significant selection in combination with corolla width, style length or stamen length. Overall floral integration was relatively high in all populations but phenotypic integration patterns were not clearly accounted by the degree of flower?pollinator mismatch or type of phenotypic selection, suggesting that trait covariation at the entire flower level is not explained by the current scenario of pollinator-mediated selection.